PENGARUH PEMBERIAN ANTIBIOTIK PROFILAKSIS TERHADAP LUARAN BEDAH PADA PASIEN GERIATRI: SISTEMATIK REVIEW - Syam, Ricky Aditya (Jurnal Buana Farma, 2025)
This systematic review examined the effectiveness of prophylactic antibiotic administration in reducing the risk of surgical wound infection in geriatric patients. This topic is of particular importance globally given the rapid increase in the elderly population susceptible to postoperative complications, as well as the variability of the existing evidence regarding the effectiveness and optimal duration of prophylactic antibiotics. Although many studies have been conducted, there has not been a comprehensive synthesis of recent evidence to fill the gap. This study, which is a systematic review based on the PRISMA 2020 guidelines, analyzes articles from the Scopus, PubMed, and Google Scholar databases (2020-2025). The study involved 31 articles that met the inclusion criteria, including retrospective observational studies and randomized clinical trials, with the primary outcomes of postoperative infections and antibiotic-related side effects. The analysis method includes evaluation of the quality of the study as well as narrative and quantitative synthesis. The results showed that the administration of prophylactic antibiotics appropriately significantly reduced the risk of infection, especially in high-risk surgeries such as colorectal, orthopedic, and cardiothoracic, with an optimal duration of about 24 hours postoperatively. The risk of antibiotic resistance and opportunistic infections remains a major concern. The practical implications demand the development of evidence-based guidelines with adjustments to the duration of administration and the strengthening of alternative prevention strategies. Advanced research with a multicenter randomized clinical trial design is essential to optimize prophylactic regimens in diverse and complex elderly populations.